The Importance of Establishing a Lokpal in India; Lokpal Vitality in Democracy-Device for Combating Administrative Lawlessness - Shrishaila Mudhol (Current Approaches in Science and Technology Research Vol. 10, 2021)
Corruption is a complex issue that is entwined with bureaucratic rigidity, issues of economic access, and political power; in this sense, the state is the primary promoter of corruption; it cannot be reduced to a question of morality alone, and the existing mechanisms for checking elected and administrative officials have not been effective., as growing instances of corruption cases suggest, and existing CVC-central vigilance commission is designed to inquire into allegations of corruption and the CBI, the premier investigation agency of the country functions under the supervision of the ministry of personnel public grievances (under the prime minister) and As a result, it is not immune to political pressure during investigations; indeed, the CBI's lack of independence and professionalism has frequently been castigated by the Supreme Court in recent times; all of this has necessitated the establishment of Lokpal with its own investigating team as soon as possible. There is a revolution in India, an anti-corruption wave is growing within Indian civil society; in latest years, people from all walks of life have said: enough is enough, and each in their own way is doing something about it; some are taking to the streets, as we have seen the Jan Lokpal movement under the leadership of Anna Hazaare and his team has truly awakened the entire nation about administrative lawlessness. and They demanded that their suggestions be incorporated into the Lokpal bill, and their effort to live a democratic life has received widespread support. Others are fighting this through the courts, while others have turned to the media., but Still, specific measures are required to combat rising corruption in all sectors; strong and stringent laws must be enacted with teeth and power, leaving no room for the guilty to flee; and firm and strong steps must be taken in the implementation of LOKPAL.